Tracing the Connection of Iron and Copper in Chronic Telogen Effluvium: Iron and Copper in Chronic Telogen Effluvium - Zufishan, Shayan; Rafique, Sara; Nasir, Faiza; Amir, Erum; Nazar, Shazia; Bandhani, Asma (Pakistan Journal of Health Sciences, 2024)
Chronic Telogen Effluvium (CTE) is a common non- scarring, diffuse type of hair loss, affecting a significant proportion of population. The purpose of the current study is to assess the relationship between CTE and trace metal levels, specifically copper and iron. Objective: To collect hair and serum samples from both control group and patients with CTE and to analyze the association between hair copper and iron content and serum copper and iron levels in both groups. Methods: The Dow University Hospital (DUHS) in Karachi, Sindh, Pakistan, served as the site of this case control research. The duration of study was one year. The study population encompassed hundred individuals, categorized into 50 cases with CTE and 50 healthy controls. Using non probability sampling technique (convenient sampling), the sample size was determined. Diagnostic criteria a positive hair pull test. Hair and serum samples were collected from both groups for trace metal analysis. Analysis was carried out using ab Atomic Absorption Spectrophotometer (Perkin Elmer Analyst 800, located in Waltham, MA, USA). Data analysis was carried out using SPSS® software for Windows® version 16.0. Results: Results showed that hair samples from patients had considerably lower iron levels than those from controls (p<0.001), while there was no significant difference in copper levels (p=0.713). Additionally, the CTE group showed noticeably greater copper levels (p<0.001) and significantly lower serum iron levels (p<0.001). Conclusions: The study identified a positive association between iron deficiency and hair loss.